Lung Protective Ventilation during Pregnancy: An Observational Cohort Study - Kislovskiy, Yasaswi; Hauspurg, Alisse; Donadee, Chenell; Sakamoto, Sara; Murugan, Raghavan (American Journal of Perinatology Reports, 2024)
Objectives We sought to describe characteristics of mechanically ventilated pregnant patients, evaluate utilization of low-tidal-volume ventilation (LTVV) and high-tidal-volume ventilation (HTVV) by trimester, and describe maternal and fetal outcomes by ventilation strategy.Study Design This is a retrospective cohort study of pregnant women with mechanical ventilation for greater than 24 hours between July 2012 and August 2020 at a tertiary care academic medical center. We defined LTVV as average daily tidal volume 8 mL/kg of less of predicted body weight, and HTVV as greater than 8 mL/kg. We examined demographic characteristics, maternal and fetal characteristics, and outcomes by ventilation strategy.Results We identified 52 ventilated pregnant women, 43 had LTVV, and 9 had HTVV. Acute respiratory distress syndrome occurred in 73% (N = 38) of patients, and infection was a common indication for ventilation (N = 33, 63%). Patients had LTVV more often than HTVV in all trimesters. Obstetric complications occurred frequently, 21% (N = 11) experienced preeclampsia or eclampsia, and among 43 patients with available delivery data, 60% delivered preterm (N = 26) and 16% had fetal demise (N = 7).Conclusion LTVV was utilized more often than HTVV among pregnant women in all trimesters. There was a high prevalence of maternal and fetal morbidity and fetal mortality among our cohort.Key Points
Keywords: mechanical ventilation; obstetric; low-tidal-volume ventilation; respiratory illness; pregnancy